Venomous Marine Fish: Osteichthyes (Bony Fish) - Haddad, Vidal [UNESP]; Lima, Carla; Lopes-Ferreira, Monica; Haddad, V; Tubaro, A.; Kim, E.; Kem, W. R.; Gopalakrishnakone, P. (Springer, 2016)
The authors discuss the presence of the toxins and envenomations caused by marine bony fish, a very common cause of injuries in fishermen and bathers. The most important families of marine venomous fish are commented, and the biochemical characteristics of the venoms and clinical/therapeutical aspects of the envenomations are cited. The authors emphasize their studies on toadfish, scorpionfish, and marine catfish, the fish most frequently associated with human injuries.